The dynamics of local hiv-1 epidemics: the colombian and belgian cohorts (2014)
We aimed to characterize the HIV-1 epidemic of the Belgian and Colombian cohorts using an integrated approach that includes socio-demographic information, clinical data, and viral sequences, analyzed with statistical and phylogenetic approaches.